Pengaruh Temperatur, Waktu, dan Aditif Dalam Pembuatan Zircon Micronized - Sajima, Sajima; Moch Setyadji (EKSPLORIUM, 2017)
Research on temperature, time and additives effects on milling process in micronized-zircon production has been conducted. The production of zircon micronized started from sorting process on mining products then followed by beneficiation, roasting, leaching, dryng and milling processes. The results showed that the optimum conditions of the roasting process was at the temperature of 425 °C, in 25 minutes and using 4% additives. In these conditions, micronized zircon (2 µm) obtained as much as 92.10% in10 minutes milling time.